The Hubungan Faktor Sosial Orang Dengan HIV/AIDS Dengan Akses Pelayanan Antiretroviral Selama Pandemi COVID-19 Di Kabupaten/Kota Kediri - Forman Novrindo Sidjabat; Betty Lania Arrumasari; Ni Putu Priyanka Ayu Ratnanggana; Silvia Tri Ambarwati (Majalah Kedokteran Indonesia, 2021)
Introduction: There has been a decrease in access to antiretroviral (ARV) services due to concerns of PLHIV infected with COVID-19, recommendations for quarantine by the government and health facility functions that are focused on dealing with the COVID-19 emergency. This study aims to determine the relationship between social factors of people living with HIV/AIDS and access to ARV services during the COVID-19 pandemic in Kediri Regency/City. Method: This study used a cross-sectional design with 107 respondents. Variables of social factors are relationship status, social support, residence status and peer community participation. The variable of access to ARV services is the act of visiting ARV services independently during a pandemic. Data were collected used snowball sampling techniques by online questionnaires and analyzed by chi-square test. Result: The majority of the respondents were 26-35 years old (57.9%), male (56.1%), and heterosexual (74.8%). Variables that had a significant relationship with access to ARV services included relationship status (p less than 0.05), social support (p less than 0.05), and residence status (p less than 0.05). Meanwhile, no significant relationship was found between the peer community participation variable and access to ARV services (p = 0.69). Conclusion: There was a relationship between social factors including relationship status, social support, and residence status of people living with HIV/AIDS with access to ARV services during the pandemic. It is necessary to engage and strengthen the social role of the community, especially families, by providing training and education related to understanding about HIV/AIDS, the needs and motivations of PLWHA